Resources and Productive Organizational Energy: The Mediation of Motivation at Work - Gabardo-Martins, Larissa (2024)
Based on the JD-R Model, the objective was to test the mediation of motivation at work in the relations of autonomy at work and self-efficacy at work with productive organizational energy. The sample consisted of 464 Brazilian workers, of both sexes. The results of Structural Equation Modeling showed a relationship between autonomy at work and self-efficacy at work with productive organizational energy, and demonstrated the mediation of motivation at work. Such findings offer different theoretical and practical contributions to the area of Organizational Psychology by contributing to the planning and implementation of strategies that can increase employee performance and provide a competitive advantage for organizations that invest in their human capital.